2012
DOI: 10.1177/2042018812471070
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and rheumatoid arthritis

Abstract: Objectives: Vitamin D deficiency has been implicated in the pathogenesis of autoimmune diseases, such as diabetes mellitus type 1 and multiple sclerosis. Reduced vitamin D intake has been linked to increased susceptibility to the development of rheumatoid arthritis (RA) and vitamin D deficiency has been found to be associated with disease activity in patients with RA. The objective was to evaluate vitamin D status in patients with RA and to assess the relationship between vitamin D levels and disease activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 33 publications
7
74
2
3
Order By: Relevance
“…So, other studies with a larger patient number should also be considered. Our findings are in concordance with the findings by Kostoglou-Athanassiou, et al [12], Rossini, et al [10], Haque and Bartlett [11]. Also, Welsh, et al [30], Cutolo, et al [31] and Kerr and colleagues [32] stated that 25-OH vitamin D deficiency is linked with increased disease activity in RA.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…So, other studies with a larger patient number should also be considered. Our findings are in concordance with the findings by Kostoglou-Athanassiou, et al [12], Rossini, et al [10], Haque and Bartlett [11]. Also, Welsh, et al [30], Cutolo, et al [31] and Kerr and colleagues [32] stated that 25-OH vitamin D deficiency is linked with increased disease activity in RA.…”
Section: Discussionsupporting
confidence: 83%
“…Vitamin D is known to induce immunologic tolerance and its deficiency may increase the risk of development of autoimmune diseases such as RA [12] Also, vitamin D has immunomodulatory properties. It appears to regulate the immune response by decreasing antigen presentation, inhibiting the T-helper type-1 (Th-1) cell that is directed against self-antigens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was shown that vitamin D addition prevented the onset and progress of inflammatory arthritis in rats [7,8]. However, there are different opinions about the relationship between vitamin D levels and disease activities in RA and AS patients in the literature [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Hypovitaminosis D could be associated with osteoporosis because a fall in circulating 25-hydroxy vitamin D levels into the 25-50 nM range induces secondary hyperparathyroidism that consequently increases osteoclastic bone resorption [25].…”
Section: Bone Disordersmentioning
confidence: 99%